Insulin-like growth factor binding protein-4 and -5 modulate ligand-dependent estrogen receptor-a activation in breast cancer cells in an IGF-independent manner - Hermani, Alexander; Shukla, Ashish; Medunjanin, Senad; Werner, Haim; Mayer, Doris (Cellular signalling, 2013)
Insulin-like growth factor binding proteins (IGFBPs) are modulators of numerous cellular processes including cell proliferation. Although IGFBPs classically act by sequestration of extracellular insulin-like growth factors (IGFs), thereby contributing to the fine-tuning of growth factor signals, IGF-independent actions of IGFBPs have also been described. In the breast, growth factor signaling in association with estradiol (E2)-stimulated estrogen receptor function is organized in a complex cross-talk. The importance of phosphatidylinositol 3-kinase/protein kinase B (Akt/PKB) pathway components for the E2-induced activation of estrogen receptor-alpha (ERα) is well accepted. Here we show that in the absence of IGFs, IGFBP-4 or IGFBP-5, either overexpressed in MCF-7 breast cancer cells or added exogenously, decreased the capability of E2 to induce ERα transcriptional activity. In addition, overexpression or addition of recombinant IGFBP-4 or IGFBP-5 resulted in reduction of E2-induced phosphorylation of Akt/PKB, GSK-3α/β and ERα in MCF-7 cells. The activation of the Akt/PKB-pathway describes a non-genomic effect of E2, which did not involve activation/phosphorylation of the IGF-I receptor (IGF-IR). Furthermore, knockdown of the IGF-IR did not affect the inhibition of E2-induced ERα phosphorylation by IGFBP-4 and 5. Moreover, IGFBP-4 and IGFBP-5 strongly decreased E2-triggered growth of MCF-7 cells. Our data suggest that IGFBPs interfere with the E2-induced activation of the Akt/PKB-pathway and prevent full hormone-dependent activation of ERα and breast cancer cell growth in an IGF- and IGF-IR-independent manner.
Gesehen am 05.01.2022